Performance variability, impulsivity errors and the impact of incentives as gender-independent endophenotypes for ADHD - Uebel, Henrik (2009)
BACKGROUND: Attention-deficit hyperactivity disorder (ADHD) is one of the most common and highly heritable child psychiatric disorders. There is strong evidence that children with ADHD show slower and more variable responses in tasks such as Go/Nogo tapping aspects of executive functions like sustained attention and response control which may be modulated by motivational factors and/or state-regulation processes. The aim of this study was (1) to determine if these executive functions may constitute an endophenotype for ADHD; (2) to investigate for the first time whether known modulators of these executive functions may also be familial and (3) to explore whether gender has an impact on these measures. METHODS: Two hundred and five children with ADHD combined type, 173 nonaffected biological siblings and 53 controls with no known family history of ADHD were examined using a Go/Nogo-Task in the framework of a multi-centre study. Performance-measures and modulating effects of event-rate and incentives were examined. Shared familial effects on these measures were assessed, and the influence of gender was tested. RESULTS: Children with ADHD responded more slowly and variably than nonaffected siblings or controls. Nonaffected siblings showed intermediate scores for reaction-time variability, false alarms and omission errors under fast and slow event rates. A slower event-rate did not led to reduced performance specific for ADHD. In the incentive condition, mean reaction times speeded-up and became less variable only in children with ADHD and their nonaffected siblings, while accuracy was improved in all groups. Males responded faster, but also committed more false alarms. There were no interactions of group by gender. CONCLUSIONS: Reaction-time variability and accuracy parameters could be useful neuropsychological endophenotypes for ADHD. Performance modulating effects of incentives suggested a familially-driven motivational dysfunction which may play an important role on etiologic pathways and treatment approaches for ADHD. The effects of gender were independent of familial effects or ADHD-status, which in turn suggests that the proposed endophenotypes are independent of gender.